CLINICAL SIGNIFICANCE OF HEMOCIRCULATORY ANGIOARCHITECTONY OF THE HEART FOR THE ISSUES OF TREATMENT STRATEGY IN CORONARY HEART DISEASE - V. E. Milyukov; E. N. Dolgov; T. S. Zharikova (Российский кардиологический журнал, 2014)
Coronary heart disease is higly prevalent in many world countries including Russia, and for several decades cardiovascular disease are being the main reason for death and are regarded as serious medico-social problem. Rapid development of cardiosurgery, invention and enhancement of diagnostic and endovascular interventions require not only a perfect knowledge of surgical heart vessels anatomy, but knowledge of antropometric parameters of hemocirculatory angioarchitectonic and morphological changes of myocardium. In the literature we could not find the data on principles of morphometric parameters of coronary vessels and structurally-functional condition of myocardial cells. So to say, the complex scientific studies required in this area to improve the diagnostic value and objectivity of indication to treatment methods, optimization and correction of surgical methods to improve quality of cardiovascular patients' care.